Aerobic cost in elite female adoslescent swimmers - Unnithan, V.; Holohan, J.; Fernhall, B.; Wylegala, J.; Rowland, T.; Pendergast, D. R. (International Journal of Sports Medicine, 2009)
Maximal performance in swimming depends on metabolic power and the economy of swimming. Thus, the energy cost of swimming (economy=VO2/V, Cs) and maximal aerobic power (VO2max) in elite young female swimmers (n=10, age: 15.3±1.5 years) and their relationships to race times (50-1 000 m) and national ranking were examined. V?O2 increased exponentially with velocity (V), (VO2=5.95+(-10.58 V)+5.84 V2) to a maximal V?O2 of 2.71±0.50 L·min-1 (46.7±8.2 mL·kg-1·min-1) at a free swimming velocity of 1.37±0.07 m·s-1. Cs was constant up to 1.2 m·s-1 (21.5 mL·m-1), however was significantly higher at 1.36 m·s-1 (27.3 mL·m-1). Peak [La] was 5.34±2.26 mM. Cs expressed as a percentage of Cs at maximal swimming velocity was significantly correlated with race times and ranking across a number of distances. The data for these elite females demonstrate that the energy cost of swimming is a good predictor of performance across a range of distances. However, as swimming performance is determined by a combination of factors, these findings warrant further examination.